A novel functional lignin-based filler for pyrolysis and feedstock recycling of poly(l-lactide). Issue 8 (21st March 2018) - Dai, Lin; Liu, Rui; Si, Chuanling
Abstract : Poly(d -lactic acid)-grafted lignin can add functionality, reduce cost, and enhance recyclability of poly(l -lactide). Abstract : Poly(l -lactide) (PLLA) is one of the most attractive environmental-friendly polymer. However, it has some drawbacks that are difficult to avoid such as high cost, single-function, and particularly racemization of lactide during the recycling process. Previously, lignin- graft -poly(d -lactic acid) (LG- g -PDLA) was reported with UV blocking capability, good compatibility and the ability to accelerate crystallization in PLLA systems. Upon further research, we noted an unexpected effect of this copolymer on the thermal degradation andl -lactide recovery of PLLA. Herein, to clarify the effects of LG- g -PDLA in PLLA pyrolysis, a PLLA/LG- g -PDLA blend film was prepared. The pyrolysis products, thermal degradation kinetics and mechanism of the blend film were studied in detail via thermogravimetric analysis (TGA) and pyrolysis-gas chromatography/mass spectroscopy (Py-GC/MS). During pyrolysis, the LG- g -PDLA fragments possessing free-radicals condense with the carboxyl ends of PLLA. PLLA could effectively undergo unzipping depolymerization to avoid racemization and produce more optically purel -lactide. This is the first report of a lignin-based filler with multifunction. In addition to adding properties and enhancing the performances of PLLA application, the PLLA/LG- g -PDLA blend system also presents a good example of completely green materials for feedstock recycling.